1995
DOI: 10.1002/1097-0142(19950515)75:10<2442::aid-cncr2820751009>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of atrial natriuretic peptide and vasopressin by small cell lung cancer

Abstract: Background. Hyponatremia in patients with small cell lung cancer (SCLC) is a common clinical problem usually attributed to tumor secretion of arginine vasopressin (AVP). It recently was shown that some SCLC cell lines produce atrial natriuretic peptide (ANP). The purpose of this investigation was to determine the frequency and clinical consequences of secretion of ANP by SCLC and the relative contribution of ANP and AVP to the hyponatremia associated with this disease. Methods. Levels of ANP and AVP were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…The NF2C cell line in particular might be a useful model delineating regulatory mechanisms that modulate rPPT promoter activity in neurons. The RIN cell lines might represent the dysregulation of rPPT promoter activity seen in tumours that exhibit a neuroendocrine phenotype [23][24][25][26] or they might reflect some developmental regulatory mechanisms operating on the rPPT promoter [21]. It is likely that the NF2C cells will be of more general use for analysis of neuronal gene expression because they have been reported to up-regulate the expression of neuronal markers on differentiation at 39 mC.…”
Section: Discussionmentioning
confidence: 99%
“…The NF2C cell line in particular might be a useful model delineating regulatory mechanisms that modulate rPPT promoter activity in neurons. The RIN cell lines might represent the dysregulation of rPPT promoter activity seen in tumours that exhibit a neuroendocrine phenotype [23][24][25][26] or they might reflect some developmental regulatory mechanisms operating on the rPPT promoter [21]. It is likely that the NF2C cells will be of more general use for analysis of neuronal gene expression because they have been reported to up-regulate the expression of neuronal markers on differentiation at 39 mC.…”
Section: Discussionmentioning
confidence: 99%
“…Despite previous reports which have shown the ectopic tumor production of ANP mRNA (14,15), ANP immunoreactivity in tumor cells and supernatant (16,17), and reports of resolution of hyponatremia following surgical resection of ANP expressing tumors (16), no consistent prospective associations between elevated plasma ANP and hyponatremia have been reported in patients with lung cancer (4,15,16). Two studies of ANP in plasma and tumor cell lines showed no relationship between high levels of ANP and hyponatremia in patients with lung cancer (15,16).…”
Section: Discussionmentioning
confidence: 81%
“…Two studies of ANP in plasma and tumor cell lines showed no relationship between high levels of ANP and hyponatremia in patients with lung cancer (15,16). This has been explained, in part, by the potential effect which sodium intake has on ANP levels, causing wide variations in previously studied patients (22,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extrinsic pharmacologic agents (e.g., diuretics and vasodilators) are well-known causes of OH as noted above; however the possibility exists that intrinsic neurohumoral agents with similar properties may be a contributing factor was initially suggested by observations in certain paraneoplastic syndromes; specifically, findings in small cell lung cancer in which elevated ANP was associated with OH [24].…”
Section: Wwwcardiologyjournalorgmentioning
confidence: 98%